Redirected walking for exploration of unknown environments - Lutfallah, Mathieu; Ketzel, Marco; Kunz, Andreas (Frontiers in Virtual Reality, 2024)
Real walking is the most natural locomotion method for exploring Virtual Environments (VE), enhancing the immersion of Virtual Reality (VR). Redirected Walking (RDW) is employed to enable real walking within limited tracking spaces in large VEs by subtly manipulating the mapping between the virtual and real environments. However, the effectiveness of RDW is greatly influenced by the convex shape and size of the manually defined physical tracking space, subsequently impacting the user's immersive experience. To improve performance, one strategy is to integrate exploration methods from mobile robotics with RDW. This will expand the usable tracking space, facilitating dynamic environments and rapid exploration. For this, we adapted a Unity framework for an RDW algorithm to facilitate simulations for such an exploration. We conducted a simulation with artificially created non-convex explorable tracking spaces and prerecorded path elements, simulating two adapted RDW artificial potential field (APF) concepts.Three conceptualized modes were applied: repulsive APF, exploration APF, and exploration APF with a distance threshold. Additionally, one APF was extended with a frontier-based exploration approach that utilized the path between the user's position and a targeted frontier. The analysis revealed a significant trade-off between exploration and immersion. APF combined with frontierbased the exploration technique showed the fastest exploration speed, but -however -resulted in the lowest distance between resets.